2020
DOI: 10.1186/s12879-020-05523-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of an in-house duplex PCR assay targeting the IS6110 and rpoB genes for tuberculosis diagnosis in Cameroon

Abstract: Background Tuberculosis (TB) remains a major public health concern in many low-income countries accounting for approximately two-thirds of deaths in people living with human immunodeficiency virus (HIV) infection. With prompt, accurate and appropriate treatment, almost all TB disease can be cured. The present study was to evaluate the diagnostic performance of an in-house duplex PCR (D-PCR) using IS1610 and rpoB specific primers in sputum samples from TB suspected patients. Methods A hospital-based cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It is possible that the bacillary load was too low to be detected by multiplex PCR, or there were some unrecognized PCR inhibitors in the samples. 13 These samples reiterate the role of culture as an important part of TB diagnosis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible that the bacillary load was too low to be detected by multiplex PCR, or there were some unrecognized PCR inhibitors in the samples. 13 These samples reiterate the role of culture as an important part of TB diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…These findings are supported by other recently published reports. For example, one report from Meriki et al 13 found the sensitivity and specificity of duplex PCR assay for all samples to be 93.5 and 94%, respectively; and for smear-negative culture positive samples, the sensitivity was 87.5%. Furthermore, a systematic review and meta-analysis to assess the overall accuracy of RT-PCR assay for TB diagnosis in different samples for individuals with active pulmonary and extrapulmonary infection 14 reported pooled sensitivity of 0.96 and pooled specificity of 0.92.…”
Section: Discussionmentioning
confidence: 99%
“…This higher positivity rate of IS 6110 -specific PCR over that of GeneXpert might be associated with a low concentration of target DNA in some samples owing to the uneven distribution of the microorganisms in clinical specimens and the presence of a moderately high quantity of human DNA, which is considered a common problem with the GeneXpert detection system ( Manke et al 2017 ; Meriki et al 2020 ). On the other hand, the IS 6110 , with a multiple-copy element within the tuberculosis genome, facilitates its detection by specific PCR in clinical samples even at a low concentration of target DNA ( Gonzalo-Asensio et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%